Critical policy analysis in education: Exploring and interrogating (in)equity across contexts: Special issue introduction - Diem, Sarah; Brooks, Jeffrey S. (Education Policy Analysis Archives, 2022)
This article is the introduction to a special issue of Education Policy Analysis Archives entitled, “Critical Policy Analysis in Education: Exploring and Interrogating (In)Equity Across Contexts.” The special issue presents contemporary critical policy analyses from the United States, Canada, and Australia, which collectively represent methodological, contextual, and theoretical diversity. Individually, they offer incisive critiques of policy processes and outcomes that shape the way equity, and indeed inequity, are manifest in situ. The articles represent a spectrum of approaches to understanding (in)equity in education and point out various ways that educators, scholars, policymakers, and activists can engage with systems to leverage change. In the article, the co-editors identify key themes that distinguish the special issue’s contribution and explain the importance of critical policy analysis as a relevant and necessary alternative to policy analyses that ignore issues of equity, social justice, and oppression.